Review Paper on Big Data Tools and Techniques (International Journal of Engineering and Computer Science, 2017)
In this paper we discussed about most emerging field of computer science engineering name as Big Data. This paper provides you detailed information about big data from basic to advance level. In this paper we describe about massive amount of structured, unstructured and semi structured because big data related to gathering and analysis of huge amount of data and analysis of data in this paper we also discussed about tools such as (Hadoop and HIVE) used in big data. This paper provides you deep insights about big data and various area of research available in this field.